The role of Lu doping on microstructural and superconducting properties of Bi2Sr2CaLuxCu2Oy superconducting system - Öztürk, Özgür; Aşıkuzun, Elif; Yıldırım, Gürcan (Springer Science and Business Media LLC, 2012)
Lutetium (Lu) added Bi2Sr2CaLuxCu2Oy superconducting samples with x = 0, 0.1, 0.3, 0.5, 0.7 and 1.0 are prepared by solid-state reaction method and annealed at 840 °C for 50 h. The heating and cooling rates of the furnace are adjusted to be 10 and 3 °C/min, respectively. For the comparison, undoped sample is subjected to the same annealing conditions. The prepared samples are characterized using X-ray powder diffraction (XRD), scanning electron microscope (SEM), energy dispersive spectroscopy (EDS), and dc resistivity (ρ−T) measurements. The volume fraction, grain size, texturing and lattice parameters are determined from the XRD measurements. The microstructure, surface morphology and element composition analysis of the samples produced are investigated by SEM and EDS measurements, respectively. Moreover, the resistivity (at room temperature), critical transition (onset and offset) temperature, variation of transition temperature and hole carrier concentration values of the samples studied are estimated from the dc resistivity measurements. According to the results obtained, the samples prepared exhibit the polycrystalline superconducting phase with less intensity of diffraction lines with the enhancement in the Lu addition due to the effect of the minor phase (Bi-2201). The lattice parameter c and volume fraction of Bi-2212 phase reduce systematically whereas the cell parameter a and minor phase fraction enhance with ascending the Lu content in the system, leading to the decrement in the superconducting properties. Scanning electron microscope measurements show that not only do the surface morphology and grain connectivity degrade but the grain sizes of the samples decrease with the increase of the Lu addition, as well. Energy dispersive spectroscopy results reveal that the Lu3+ ions might enter into the crystal structure by replacing Sr2+ ions, confirming why the superconducting properties of the pure sample are more superior to the samples doped. At the same time, dc resistivity results obtained show that the room temperature resistivity systematically increases with the enhancement of the Lu content as a result of the hole filling when the onset (T ) and offset (T ) temperatures determined from the resistivity curves decrease from 99.5 to 93.0 K and 85.0 to 60.0 K, respectively, illustrating not only the increment in the relative percentage of Bi-2201 phase formation and the reduction of the mobile carrier concentration but also the presence of impurities and weak links between the superconducting grains.
Keywords: 7. Clean energy